Sport : Readings from a Sociological Perspective - Dunning, Eric (Book collections on Project MUSE., 1972)
Sport is something rather taken for granted and little studied as part of man's and society's behaviour. This collection of essays, many of which appear in print for the first time, provides an international comparative and developmental orientation to the sociology of sport, thereby clarifying the nature of modern sports and their central structural and functional characteristics. The sports treated include football, soccer, rugby, wrestling, baseball, and bull-fighting, and some historical background is given on the development of sport. In the introduction to each section, the editor explains the questions that the selections are intended to illustrate, and treats briefly such matters as theories of sport and play, the social factors in their development, sport and socialization, class and race in sport, sport as an occupation and an industry, and conflict and social control in sport. This reader will be of interest to those professionally concerned, either as teacher or student, with sociology and physical education, but it should also appeal to athletes, sports-lovers, and sports commentators who like to keep their thinking in good shape too.